2017
DOI: 10.1021/acsomega.7b00409
|View full text |Cite
|
Sign up to set email alerts
|

Short Pulse Laser Synthesis of Transition-Metal Dichalcogenide Nanostructures under Ambient Conditions

Abstract: The study of inorganic nanometer-scale materials with hollow closed-cage structures, such as inorganic fullerene-like (IF) nanostructures and inorganic nanotubes (INTs), is a rapidly growing field. Numerous kinds of IF nanostructures and INTs were synthesized for a variety of applications, particularly for lubrication, functional coatings, and reinforcement of polymer matrices. To date, such nanostructures have been synthesized mostly by heating a transition metal or oxide thereof in the presence of precursor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Two different areas are there to classify the laser ablation i. e. laser ablation in liquid (LAL) and laser ablation in a vacuum (LAV). In chemistry, particular interest is the possibility of producing nano‐dispersed materials by LAL and film materials by LAV . Laser fragmentation method has been used by Chubilleau and co‐workers, the impact of various parameters such as treatment period, wavelength and output energy were studied for the fragmentation yield, crystallographic structures and size of PbTe nanoparticles.…”
Section: Synthetic Methods For Metal Telluride Nanomaterialsmentioning
confidence: 95%
See 1 more Smart Citation
“…Two different areas are there to classify the laser ablation i. e. laser ablation in liquid (LAL) and laser ablation in a vacuum (LAV). In chemistry, particular interest is the possibility of producing nano‐dispersed materials by LAL and film materials by LAV . Laser fragmentation method has been used by Chubilleau and co‐workers, the impact of various parameters such as treatment period, wavelength and output energy were studied for the fragmentation yield, crystallographic structures and size of PbTe nanoparticles.…”
Section: Synthetic Methods For Metal Telluride Nanomaterialsmentioning
confidence: 95%
“…In chemistry, particular interest is the possibility of producing nano-dispersed materials by LAL and film materials by LAV. [107] Laser fragmentation method has been used by Chubilleau and co-workers, the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 impact of various parameters such as treatment period, wavelength and output energy were studied for the fragmentation yield, crystallographic structures and size of PbTe nanoparticles. The average diameter for PbTe nanoparticles was 4-6 nm in liquid medium.…”
Section: Other Synthetic Methodsmentioning
confidence: 99%
“…The laser annealing method is using laser as a heating source to promote the synthesis reaction between different precursor species. For instance, Tenne et al [87] creatively used ultrashort-pulse laser to process a mixture of bulk transition-metal dichalcogenides and Pb/PbO to fabricate [77]. i Illustration of the laser pyrolysis process of N-doped SnO 2 [74].…”
Section: Metal Disulfidesmentioning
confidence: 99%
“…The laser annealing method is using laser as a heating source to promote the synthesis reaction between different precursor species. For instance, Tenne et al [ 87 ] creatively used ultrashort-pulse laser to process a mixture of bulk transition-metal dichalcogenides and Pb/PbO to fabricate inorganic fullerene-like and nanotube-like TMDs nanostructures, the catalytic effects of metal assisted with the ultrafast laser-induced thermal annealing contributed to the formation of different TMDs nanostructures. Lamberti et al [ 88 ] reported rapid one-pot synthesis of MoS 2 -decorated laser-induced graphene (MoS 2 -LIG) by direct writing of polyimide foils coating with a layer of MoS 2 dispersion.…”
Section: Laser As the Synthetic Techniquementioning
confidence: 99%
“…This method doesn't require nor any matrices for dispersion of nanorarticles like a polymeric (silicon) matrix for the YAG:Ce particles used in WLEDs neither heavy metal solvents as in liquid phase epitaxy method. Also the PLD method doesn't need high temperatures and additional chemical reagents for synthesis (Savva et al, 2017). All these factors can effect on luminescent efficiency of the RE-activated nanoparticles.…”
Section: Introductionmentioning
confidence: 99%